Rola banków w zarządzaniu finansami przedsiębiorstw - wybrane aspekty - Galbarczyk, Tamara (The Role of Banks in The Management of Finances of Enterprises - Selected Aspects, 2008)
When conducting economic activity, enterprises should seek the optimal capital structure. The enterprise's own funds can be supplemented by outside capital derived from banks or mercantile credit or from the issuance of short- and long-term debt securities. Excess funds of the enterprise can in turn be invested through banks or other financial institutions. The traditional form of investment of free funds is to deposit them in a bank. An alternative to bank deposits is to purchase securities issued by other entities. Despite the increased interest by enterprises in both the issuance of and investment of excess funds in debt securities, which is corroborated by figures, there is no decrease in the interest in cooperation with banks at all. As the figures show, the value of funds deposited in banks over the whole period investigated not only rose but also exceeded many times the banks' investments in treasury and non-treasury debt securities. Because the subject is very broad, our discussion did cover investment by enterprises in shares, stakes, or investment funds. More than half the funds deposited by enterprises in banks over the whole period were, moreover, low-interest current deposits. What was more important than the low profit of bank deposits was apparently the greater security of funds entrusted to the banks. Similarly, the value of loans raised from the banks, which is a classical way of outside funding, exceeded several times the amount of funds obtained by the enterprises through the issuance of debt securities. The latter form of raising capital may, however, be unavailable, especially to smaller entities.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 172-180